2010
DOI: 10.1128/jvi.01051-10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Type I Interferon Response in Human Dendritic Cells by Dengue Virus Infection Requires a Catalytically Active NS2B3 Complex

Abstract: Dengue virus (DENV) is the most prevalent arthropod-borne human virus, able to infect and replicate in human dendritic cells (DCs), inducing their activation and the production of proinflammatory cytokines. However, DENV can successfully evade the immune response in order to produce disease in humans. Several mechanisms of immune evasion have been suggested for DENV, most of them involving interference with type I interferon (IFN) signaling. We recently reported that DENV infection of human DCs does not induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 57 publications
10
127
2
1
Order By: Relevance
“…This further implies that JEV-encoded proteins are not the major components that inhibit IFN induction, contrary to what has been reported for other flaviviral proteins (24,27,36,48). In similar experiments, DENV was able to inhibit IFN activation using various inducers (36), but WNV and TBEV failed to inhibit IFN activation by poly(I ⅐ C) (6,30), suggesting that not all flaviviruses possess an active mechanism to antagonize the host IFN pathway. The intact and functional IFN system of PS cells during JEV infection reinforces the idea that the virus (i.e., dsRNA) is simply not detected at early stages of infection.…”
Section: Discussioncontrasting
confidence: 50%
“…This further implies that JEV-encoded proteins are not the major components that inhibit IFN induction, contrary to what has been reported for other flaviviral proteins (24,27,36,48). In similar experiments, DENV was able to inhibit IFN activation using various inducers (36), but WNV and TBEV failed to inhibit IFN activation by poly(I ⅐ C) (6,30), suggesting that not all flaviviruses possess an active mechanism to antagonize the host IFN pathway. The intact and functional IFN system of PS cells during JEV infection reinforces the idea that the virus (i.e., dsRNA) is simply not detected at early stages of infection.…”
Section: Discussioncontrasting
confidence: 50%
“…DENV is known to be a weak inducer of type I IFN, and DENVinfected human dendritic cells exhibit an impaired type I IFN response to infection with several viruses and to stimulation with poly(I·C) (14,44,45). Thus far, the functional significance of NS4A in viral replication remains poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DENV infection usually leads to low levels of IFN-␣ and -␤, thus suggesting that DENV may inhibit IFN production after DENV infection (12)(13)(14)(15)(16). Several research groups have reported that prevention of STAT1 phosphorylation or induction of STAT2 degradation is a mechanism possibly underlying the antagonistic effects of DENV on IFN signaling (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…These mutations contribute to a lower ability of the American genotype strains to replicate in human monocyte-derived macrophages and dendritic cells (7,38). Conversely, the five mutations we report in nonstructural proteins may interfere with viral replication (10) and inhibit type I interferon (IFN) signaling (1,31,41).…”
Section: Vol 85 2011 Denv-3 Induces Inflammatory Responses In Mddcsmentioning
confidence: 99%